2002
DOI: 10.1097/00005373-200204000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Head Injuries in Rats: Effects on Behavior

Abstract: Multiple concussions cause immediate transient impairment in spatial recognition and have extended effects on baseline performance in rats. Motor performance is not affected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
39
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 19 publications
3
39
1
Order By: Relevance
“…Furthermore, studies have now administered repeated mFPIs (rmFPI) to rats to study the effects of rmTBI, and related conditions such as CTE. Findings from these studies indicate that rmFPIs induce cumulative and persisting cognitive, sensorimotor, and emotional abnormalities that occur in the presence of progressive cortical atrophy and neuronal loss, axonal injury, chronic neuroinflammation, alterations in excitatory synaptic neurotransmission, and impaired long-term potentiation (Aungst et al, 2014;DeRoss et al, 2002;Shultz et al, 2013Shultz et al, , 2012Wang et al, 2013;Webster et al, 2015). Many of these changes resemble the spectrum of abnormalities that have been reported in humans who have suffered rmTBIs.…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Furthermore, studies have now administered repeated mFPIs (rmFPI) to rats to study the effects of rmTBI, and related conditions such as CTE. Findings from these studies indicate that rmFPIs induce cumulative and persisting cognitive, sensorimotor, and emotional abnormalities that occur in the presence of progressive cortical atrophy and neuronal loss, axonal injury, chronic neuroinflammation, alterations in excitatory synaptic neurotransmission, and impaired long-term potentiation (Aungst et al, 2014;DeRoss et al, 2002;Shultz et al, 2013Shultz et al, , 2012Wang et al, 2013;Webster et al, 2015). Many of these changes resemble the spectrum of abnormalities that have been reported in humans who have suffered rmTBIs.…”
Section: Introductionmentioning
confidence: 85%
“…Animal models allow for the rigorous investigation of pathophysiological changes (e.g., h-tau and PP2A) in mTBI and rmTBI, and for the assessment of novel pharmaceutical interventions that target these mechanisms. The single mild fluid percussion injury (mFPI) model in rats results in transient motor and cognitive deficits (DeRoss et al, 2002;Gurkoff et al, 2006;Hylin et al, 2013;Shultz et al, 2011), as well as abnormalities in sleep (Lim et al, 2013), electrophysiology (Aungst et al, 2014;Johnstone et al, 2014), and other behaviors (Shultz et al, 2011). A single mFPI also induces transient neuroinflammation, axonal injury, and reduced cerebral blood flow (Hylin et al, 2013;Shultz et al, 2012Shultz et al, , 2011, but does not result in significant neuronal loss, visible brain contusion, focal lesion, or enduring cognitive and behavioral impairments (Aungst et al, 2014;Gurkoff et al, 2006;Hylin et al, 2013;Shultz et al, 2012Shultz et al, , 2011.…”
Section: Introductionmentioning
confidence: 99%
“…DeRoss and colleagues (2002) studied repeated concussions in adult male rats and demonstrated a return baseline performance in Morris water maze by 10 to 14 days after injury. Unexpectedly, they observed a decrease in the number of trials needed to return to baseline latency in the Morris water maze with multiple concussions (DeRoss et al, 2002), perhaps attributable to a training effect. Laurer and colleagues (2001) examined a shorter inter-injury interval and demonstrated increased deficits in the adult mice that received two injuries 24 h apart compared to those with a single injury.…”
mentioning
confidence: 95%
“…Currently there is a paucity of age-specific data about mechanisms for primary traumatic brain injury in children. Furthermore, clinical studies and observations, supported by data from mice and rat models, have suggested cumulative effects of repeated mild head injury (Laurer et al, 2001;DeRoss et al, 2002;Guskiewicz et al, 2003Guskiewicz et al, , 2005McCrea et al, 2003;Longhi et al, 2005;Huh et al, 2007). Recent evidence supports that neuropsychological deficits following single and repeated mild traumatic brain injury is a common problem in adults and children (De Monte et al, 2005;Barrow et al, 2006;Iverson et al, 2006;Wall et al, 2006).…”
mentioning
confidence: 96%
“…LUCID [7][8][9] Our data indicate that the initial neurologic presentation of children with fatal head injury also depended on age. In the youngest children (Ͻ24 months old), those with inflicted injury were 10 times more likely to present with a moderate GCS score than those in MVCs.…”
mentioning
confidence: 66%